Atherosclerosis and Atheroma Plaque Rupture: Imaging Modalities in the Visualization of Vasa Vasorum and Atherosclerotic Plaques - Sun, Zhonghua (Hindawi Publishing Corporation, 2014)
Invasive angiography has been widely accepted as the gold standard to diagnose cardiovascular pathologies. Despite its superior resolution of demonstrating atherosclerotic plaque in terms of degree of lumen stenosis, the morphological assessment for the plaque is insufficient for the analysis of plaque components, and therefore, unable to predict the risk status or vulnerability of atherosclerotic plaque. There is an increased body of evidence to show that the vasa vasorum play an important role in the initiation, progression, and complications of atherosclerotic plaque leading to major adverse cardiac events. This paper provides an overview of the evidence-based reviews of various imaging modalities with regard to their potential value for comprehensive characterization of the composition, burden, and neovascularization of atherosclerotic plaque.